Information security theory and practice. security of mobile and cyber-physical systems : 7th IFIP WG 11.2 International Workshop, WISTP 2013, Heraklion, Greece, May 28-30, 2013. Proceedings - Gollmann, Dieter; Cavallaro, Lorenzo (Lecture Notes in Computer Science, 2013)
This volume constitutes the refereed proceedings of the 7th IFIP WG 11.2 International Workshop on Information Security Theory and Practices: Security and Privacy of Mobile Devices in Wireless Communication, WISTP 2013, held in Heraklion, Crete, Greece, in May 2013. The 9 revised full papers presented together with  two keynote speeches were carefully reviewed and selected from 19 submissions. The scope of the workshop spans the theoretical aspects of cryptography and cryptanalysis, mobile security, smart cards and embedded devices.